The Role of Serum IL-23 and Volatile Organic Compound Levels to RECIST 1.1 in The Evaluation of Therapeutic Response in Lung Cancer - Tjahyadi, Rizal Muldani; Setyawan, Ungky Agus; Astuti, Tri Wahju; Djajalaksana, Susanthy; Wardoyo, Arinto Yudi Ponco (Indonesian Society for Cancer Chemoprevention, 2023)
The Response Evaluation Criteria in Solid Tumors (RECIST 1.1) is the gold standard for the assessment of lung cancer progression. However, the assessment and diagnosis of early treatment failure is challenging due to the limitations of current tools, as well as the long intervals and unavoidable side effects.This study aims to correlate volatile organic compound (VOC) patterns, serum level of interleukin-23 (IL-23), and RECIST 1.1 to assess chemotherapy response in lung cancer patients at Saiful Anwar Hospital. A prospective observational study was performed to 47 lung cancer patients who received three cycles of platinum-based chemotherapy. Using the Breath Analyzer to measure certain volatile organic compounds (VOCs), the study observed that three of the seven VOCs examined, formaldehyde (CH2O), toluene (C7H8), and hexane (C6H14), showed lower levels after three cycles of chemotherapy. Furthermore, there was a negative correlation between RECIST1.1 and acetone (C3H6O) (p=0.023), while RECIST1.1 and methane (CH4) had a positive correlation (p=0.011). Moreover, a significant positive correlation was observed between IL-23 after-chemotherapy and RECIST 1.1 (p=0.000). According to this study, a correlation exists between methane, IL-23, and RECIST 1.1 after three cycles of chemotherapy. The increase in methane and IL-23 aligns with the disease progression determined by RECIST 1.1. Furthermore, The decrease in acetone after chemotherapy showed a negative correlation with RECIST1.1, consistent with disease progression.Keywords: Volatile Organic Compound, Interleukin-23, RECIST 1.1.